Employee Engagement: QCC's Improve Productivity by Engaging Workers in Problem-Solving at CATL: A Case Study of CATL’s Headquarters and Indonesian Branch - Margaretha Sonya; Muhammad Fachri Maulana; Songrui Carl (Economics and Business Journal (ECBIS), 2026)
This study examines the implementation of the Quality Control Circle (QCC) system to enhance employee engagement and productivity at Contemporary Amperex Technology Co., Limited (CATL) headquarters and its Indonesian branch. As a global leader in lithium-ion battery manufacturing, CATL integrates innovative technology with employee participation to improve work processes and operational performance. QCC is applied as a structured approach that empowers employees to identify workplace problems, develop solutions, and collaborate in continuous improvement activities using quality management tools and the PDCA cycle. The research employs a case study and comparative analysis method to explore differences between the standardized QCC system at CATL headquarters and the more flexible, localized implementation in Indonesia. The study involved permanent employees from both organizations using saturated sampling, with a total of 10 respondents. In addition, a five-day productivity training program was conducted in China and Karawang through lectures, case studies, and project-based learning, evaluated using pre-test and post-test assessments. The findings indicate that QCC significantly improves employee understanding of productivity management, strengthens communication, enhances product quality, reduces quality-related costs, and increases employee engagement, motivation, and organizational commitment in both operational environments